2008
DOI: 10.1128/iai.00356-08
|View full text |Cite
|
Sign up to set email alerts
|

A Tripartite Efflux Pump Involved in Gastrointestinal Colonization by Klebsiella pneumoniae Confers a Tolerance Response to Inorganic Acid

Abstract: In vivo assays showed that a ⌬eefA isogenic mutant strain normally colonized the gastrointestinal tract in single-strain tests but was significantly impaired in competition against wild-type strain LM21. Although the cecum was the compartment with the highest number of CFU, the ⌬eefA mutant also was detected in the stomach in numbers smaller than those of the wild-type strain. The expression of this potential efflux pump could not be linked to any antimicrobial drug resistance phenotype, but it conferred on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…They also have shown that the K. pneumoniae AcrAB efflux system is involved in resistance to the host antimicrobial peptides present in the lung, one of the first barriers of the innate immune system against infections. This finding strongly suggests the participation of efflux systems of K. pneumoniae in its virulence, as did the results provided by Coudeyras et al that showed that the potential efflux pump EefABC of K. pneumoniae conferred an advantage to this bacterial species to colonize the digestive tract in a murine model (4).…”
supporting
confidence: 67%
“…They also have shown that the K. pneumoniae AcrAB efflux system is involved in resistance to the host antimicrobial peptides present in the lung, one of the first barriers of the innate immune system against infections. This finding strongly suggests the participation of efflux systems of K. pneumoniae in its virulence, as did the results provided by Coudeyras et al that showed that the potential efflux pump EefABC of K. pneumoniae conferred an advantage to this bacterial species to colonize the digestive tract in a murine model (4).…”
supporting
confidence: 67%
“…Nearly all tested clinical tigecycline-nonsusceptible isolates (25 out of 26) from China contained mutations in ramR and/or acrR, with about onethird of the isolates carrying the simultaneous overexpression of ramA-acrB and rarA-oqxB (301). The expression of eefABC appears to be induced by an acidic or hyperosmolar environment but not by bile salts (793). The CpxAR system and the LysR-type OxyR regulator are also involved in the positive control of the expression of the acrB, acrD, and/or eefB efflux gene (794,795).…”
Section: K Pneumoniae Efflux Pumpsmentioning
confidence: 99%
“…Multidrug efflux pumps of bacterial pathogens are involved in intrinsic and acquired resistance to antimicrobial compounds, including those naturally present at mucosal surfaces; the pumps enable bacteria to grow on such surfaces and can thus be considered as being involved in colonization (65). Moreover, multidrug efflux pumps can discharge molecules involved in the quorum-sensing-regulated expression of virulence determinants (66 (Fig.…”
Section: Ribosomal Protection Tet44mentioning
confidence: 99%